Preparation Of Palladium Nanoparticles Stabilized By Cyclodextrins In Aqueous Solution And Their Activity For Hydrogenation Of Palm Oil - Wi, Lihua; Liew, Kong Yong; Salimah, Shafii (2010)
Palladium (Pd) nanoparticles were prepared in aqueous solution with different cyclodextrins (CDs) as stabilizer and alcohols as reducing agent. An optimum condition for the preparation of Pd nanoparticles was found to involve the use of 2-propanol as reducing agent at 30oC (room temperature). UV-visible and FT-IR spectra of the products indicated the presence of interaction between CD and metallic Pd. The TEM micrographs showed that the nanoparticles were less than 30 nm in diameter. It was observed that the nanoparticles were stable as colloid solution for weeks. The CD stabilized Pd nanoparticles shows high catalytic activity towards hydrogenation reaction of palm oil at room temperature. The C18:2 in palm oil were totally hydrogenated within 20 min of reaction, while γ-CD-Pd was observed to show highest hydrogenation activity.